Evaluating SARS‐CoV‐2 airborne quanta transmission and exposure risk in a mechanically ventilated multizone office building. (1st July 2022) - Yan, Shujie; Wang, Liangzhu (Leon); Birnkrant, Michael J.; Zhai, John; Miller, Shelly L.
Abstract: The world has faced tremendous challenges during the COVID-19 pandemic since 2020, and effective clean air strategies that mitigate infectious risks indoors have become more essential. In this study, a novel approach based on the Wells-Riley model applied to a multizone building was proposed to simulate exposure to infectious doses in terms of " quanta ". This modeling approach quantifies the relative benefits of different risk mitigation strategies so that their effectiveness could be compared. A case study for the US Department of Energy large office prototype building was conducted to illustrate the approach. The infectious risk propagation from the infection source throughout the building was evaluated. Different mitigation strategies were implemented, including increasing outdoor air ventilation rates and adding air-cleaning devices such as Minimum Efficiency Reporting Value (MERV) filters and portable air cleaners (PACs) with HEPA filters in-room/in-duct germicidal ultraviolet (GUV) lights, layering with wearing masks. Results showed that to keep the risk of the infection propagating low the best strategy without universal masking was the operation of in-room GUV or a large industrial-sized PAC; whereas with masking all strategies were acceptable. This study contributes to a better understanding of the airborne transmission risks in multizone, mechanically ventilated buildings and how to reduce infection risk from a public health perspective of different mitigation strategies. Highlights: A new method was developed for simulating SARS-CoV-2 airborne quanta transmission in multizone buildings using CONTAM. Whole-building exposure risk was modeled for a large office building, considering dynamic zone pressures and ambient conditions. System level mitigation was more effective to reduce overall building risk when the location of the infected individual was unknown. In-room mitigation reduced local transmission risk more effectively when the individual was in the same zone.